Direito à Imagem - Loureiro, Henrique Vergueiro (2005)
The technological evolution in the last two centuries, allied to the development of the large scale media, the advertising and propaganda, caught the attention of the legal world for the study of the image. Initially, this legally protected interest was inserted in the guardianship of other rights, such as the right to the honor, the right to the privacy, the copyright and the right to the proper body. Afterwards it was realized that it was an independent legally protected interest, deserving proper protection, otherwise it could constitute a gap in the guardianship of the personality. Treated with disdain for the Brazilian infraconstitutional legislator, the image was raised independent by the Federal Constitution of 1988, integrant of the roll of the stony clauses and essential basic right to the dignity of the person human being. The Federal Constitution also conceived a new meaning of image - beyond the physical conformation of the individual - that aggregate the attributes presented by a person to the society. Not sharing the same view of the Federal Constitution, the Civil Code of 2002 reduced the field of protection of the image, what, in it, imposes the need to recognize the unconstitutionality of its article 20 and to invoke article 5º, V and X, of the Federal Constitution, norms of full effectiveness and immediate applicability, and article 12 of the Civil Code, general clause of guardianship of the personality, to protect this legal interest. Currently can be observed in our Superior Courts decisions that determine the repairing of pain and suffering for the mere breaking of the right to the image, independently of injury to the honor or other rights of the personality, consecrating effectively the autonomy of this basic good of the personality.